2021
DOI: 10.1021/acsami.0c17732
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles on Nanosheets Derived from Layered Rare-Earth Hydroxides for Catalytic Glycerol-to-Lactic Acid Conversion

Abstract: Layered rare-earth hydroxides (LREHs), as a series of special lamellar compounds having a similar structure to layered double hydroxides (LDHs), are becoming a new type of catalyst materials. In this study, we have prepared a series of uniform LREH (RE = Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, and Tm) nanosheets through a reverse-microemulsion method. After deposition–precipitation of HAuCl4 and calcination, supported Au catalysts (denoted as Au/LREO) were subsequently obtained. The catalytic properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Wang et al utilized coprecipitation of iron oxide and ceria to improve the adsorption performance. Compared with cerium oxide, the layered structure of cerium carbonate possesses cerium active sites that are easily accessible for the phosphate adsorption process. Enhancement in the adsorption effect could be achieved by exploiting alternative doping elements …”
Section: Introductionmentioning
confidence: 99%
“…Wang et al utilized coprecipitation of iron oxide and ceria to improve the adsorption performance. Compared with cerium oxide, the layered structure of cerium carbonate possesses cerium active sites that are easily accessible for the phosphate adsorption process. Enhancement in the adsorption effect could be achieved by exploiting alternative doping elements …”
Section: Introductionmentioning
confidence: 99%
“…Layered rare-earth hydroxide (LREH, RE = Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, and Tm) nanosheets were used as supports for the gold(0) nanoparticles. 53 The LREH nanosheets supported gold(0) nanoparticles were prepared by the deposition–precipitation of HAuCl 4 and calcination and denoted as Au/LREO. The highest glycerol conversion (68.2%) with the highest LA selectivity (66.8%) was obtained using Au/LPrO among Au/LREO catalysts at 90 °C for 14 h under aerobic conditions.…”
Section: Heterogeneous Catalysts In the Conversion Of Glycerol To Lamentioning
confidence: 99%
“…Furthermore, low reaction temperature can also significantly inhibit C–C bond cleavage by alkalis, thus good selectivity of C 3 products. Selective oxidation of glycerol to LA is generally carried out with the promotion of various noble metal and some non-noble metal catalysts (e.g., Au, Pt, Pd, and polyoxometalate ) ( Shen et al, 2010 ; Lakshmanan et al, 2013 ; Xu et al, 2013 ; Cho et al, 2014 ; Purushothaman et al, 2014 ; Zhang et al, 2016a ; Zhang et al, 2016b ; Arcanjo et al, 2017 ; Tao et al, 2017 ; Zhang et al, 2017 ; Douthwaite et al, 2020 ; Evans et al, 2020 ; Tao et al, 2020 ; Torres et al, 2021 ; Wang et al, 2021 ). In the first important advances, Shen et al (2010) reported that the bimetallic Au–Pt catalysts exhibit excellent performances with a high yield of 86% in the presence of alkali and O 2 at 90°C.…”
Section: Catalytic Conversion Of Glycerol To Lamentioning
confidence: 99%